State Taxation of Interstate Commerce - Charles Harper Anderson (Washington University Law Quarterly, 1952)
The United States Supreme Court has been confronted with numerous issues which require a reconciliation of the principle of maintaining free interstate trade and that requiring persons engaged in interstate commerce to bear their share of state taxation. In deciding these issues the Court has used various words to state and explain applicable legal tests. To understand these tests the situations from which they were originated, as well as those in which they were applied, should be examined.
Keywords: Taxation -- United States; Constitutional law: U. S. -- XV. Taxation